KARAKTERISASI NANO KITOSAN CANGKANG UDANG VANNAMEI (Litopenaeus vannamei) DENGAN METODE GELASI IONIK - Pipih Suptijah; Agoes Mardiono Jacoeb; Desie Rachmania (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Shrimp shells have a potential as raw materials for manufacturing of nanochitosan. The purposes of this study to obtain the highest yield of chitosan treated by HCl immersion time, determine the best ionic gelation process with various treatments sizing, to determine the characteristics of nanoparticles e.g morphology, efficiency, and size of nanoparticles, analyze the characteristics of chitosan particles carried by the ionic gelation method using Fourier Transform InfraRed (FTIR) and Scanning Electron Microscopy (SEM), determine a simple method for making chitosan, that be applied easily in the laboratory. The highest yield of chitosan from shrimp shell obtained by treatment with 1 N HCl soaking time for 72 hours. Magnetic stirrer treatment could obtain high yield of nano chitosan with particle size 400-450 nm. Magnetic Stirrer could distribute the particle size homogeneously and stable than using of ultrasonic and high speed homogenizer. Degree of deacetylation of chitosan nanoparticles was 99%. Keyword: chitosan nano, FTIR, ionic gelation, SEM, white shrimp shells